Evaluation of precooling methods for shelf-life enhancement of pear (Pyrus spp.) fruits under ambient storage - MAHAJAN, KASHIKA; GUPTA, S K; SHARMA, S R; SINGH, NAV PREM; KANOJIA, VARSHA (The Indian Journal of Agricultural Sciences, 2023)
Patharnakh pear fruits were freshly harvested at the physiological maturity during second week of July and subjected to different precooling treatments, viz. Hydrocooling (HC), Forced Air Cooling (FAC) and Evaporative Cooling (EC). The effect of these methods on fruit shelf-life and quality attributes under ambient conditions was investigated during the year 2021–22 at Punjab Horticultural Post harvest Technology Centre, Punjab Agricultural University, Ludhiana, Punjab. In all treatments, temperature of fruit pulp was regularly checked with digital pulp thermometer until a constant temperature was accomplished. Thereafter, the fruits were packed in corrugated fibre board boxes of 2 kg capacity and stored at ambient conditions (28–32°C and 70–80% relative humidity). The stored samples were assessed, periodically, at 5 days interval till 20 days for physiological and biochemical parameters. The results of the study revealed that FAC maintained lower physiological weight loss, spoilage and retained higher fruit firmness, sensory quality score, juice TSS, total sugars, acidity, vitamin C and total phenolic content during storage compared to the control. This method is an effective approach for maintaining the post-harvest shelf-life of perishable pear fruits for about 15 days in comparison to 10 days in the untreated control fruits.